Anatomy of the neurocranium, encephalon, and main sensory organs of the roundel skate, Rostroraja texana (Rajiformes: Rajidae) (Revista de Biología Marina y Oceanografía, 2022)
The organization of the neurocranium, the encephalon, and the main sensory organs of Rostroraja texana (Family Rajidae) corresponds to the general morphological pattern of the elasmobranchs and, in particular, of the batoids. The neurocranium presents the rostrum, which corresponds to about 50% of the cranial length; additionally, it shows two dorsal fontanelles of similar shape and size. The anatomical relations of the neurocranium of R. texana are with the encephalon, the main sensory organs, the antorbital, synarcual, and spiracular cartilages, and with the mandibular, hyoid, and extra-ocular musculature. The encephalon is relatively narrow. The cerebellum is symmetrical and shows a partial division in the anterior and posterior portions. In the olfactory system, the following characteristics stand out: the external pigmentation of the olfactory organs, the high number of olfactory lamellae, and the asymmetry of the olfactory bulbs. In the optical system, the presence of the pupillary operculum and the division into two sections of the superior oblique muscle is notable. And, in the statoacoustic system, the large size of the saccular otoconia stands out.